Experimental investigation of soil pH Engineering with eco enzyme to improve grounding performance - I Wayan Jondra; Zulkurnain Abdul-Malek; I Nengah Sunaya; Made Sudana; I Made Purbhawa (Institute of Advanced Engineering and Science, 2026)
The reliability of electric power distribution, in mitigating fault and disturbances, is strongly influenced by the effectiveness of grounding systems. A key factor in achieving low grounding resistance an essential requirement per construction and safety standards is soil condition. High grounding resistance is frequently observed in field implementations and is closely linked to soil resistivity, type, stratification, moisture content, and acidity (pH). This quantitative applied research addresses the persistent challenge of high grounding resistance by experimenting with investigating six grounding system models subjected to varying soil acidity levels. The study introduces the use of eco enzyme as a natural additive to modify soil pH and examines its effect on grounding resistance. Findings reveal that eco enzyme application successfully lowers soil pH, with an optimal reduction in grounding resistance observed at pH 3.8 achieving a drop from 40 ohms to 9 ohms. However, further lowering the pH below 3.8 results in a rise in resistance, indicating a threshold where acidic conditions become counterproductive. This research opens opportunities for broader applications of eco enzyme-treated soil in non-rod electrode systems and across diverse soil types, suggesting promising pathways for enhancing grounding systems in various environmental conditions.